ANTI-CRISIS STRATEGIES FOR FORMING A POLITICAL IMAGE IN WARTIME: UKRAINIAN EXPERIENCE 2022–2024 - Maidanskyi, Ivan; Zienkin, Mykhailo (Public Management and Policy, 2025)
The article examines the transformation of political image in the context of military conflict. The political image is seen as a multi-level socio-psychological construct that is formed in the mass consciousness under the influence of both rational judgments and emotional associations, and is consolidated through the media, social networks, and personal observations. The purpose of the article is to conduct a comprehensive analysis of strategies for shaping and promoting political image from 2022 to 2024 in the context of a full-scale war. Objectives: to outline theoretical approaches to understanding political image; to analyze the conditions in which political image was formed during the full-scale war of the Russian Federation against Ukraine in 2022–2024; to analyze the key positive aspects of political image formation and identify critical mistakes and weaknesses of communication strategies that could negatively affect the image of the head of state and institutions of Ukraine in general; to formulate generalized conclusions about the effectiveness of strategic communications in shaping political image in the context of a full-scale war. Particular attention is paid to the role of strategic communications as a means of forming a state-centered narrative in times of war, when information, semantic, and cognitive warfare are no less important than military operations. Using the case of V. Zelenskyy as an example, the article analyzes the strengths of his media image – adaptability, personalization, empathy, effective digital communication – as well as critical challenges: excessive personalization of the state position, communication mistakes in times of crisis. It is concluded that in the current conditions of war and global change, the political image of a leader is not only an element of political advertising, but also an instrument of national mobilization, international support and societal resilience. The generalized experience of Ukraine can be useful for countries that find themselves in a state of external aggression and need an effective communication strategy.